Development of CDK2 and CDK5 Dual Degrader TMX‐2172. Issue 33 (3rd June 2020) - Teng, Mingxing; Jiang, Jie; He, Zhixiang; Kwiatkowski, Nicholas P.; Donovan, Katherine A.; Mills, Caitlin E.; Victor, Chiara; Hatcher, John M.; Fischer, Eric S.; Sorger, Peter K.; Zhang, Tinghu; Gray, Nathanael S.
Abstract: Cyclin‐dependent kinase 2 (CDK2) is a potential therapeutic target for the treatment of cancer. Development of CDK2 inhibitors has been extremely challenging as its ATP‐binding site shares high similarity with CDK1, a related kinase whose inhibition causes toxic effects. Here, we report the development of TMX‐2172, a heterobifunctional CDK2 degrader with degradation selectivity for CDK2 and CDK5 over not only CDK1, but transcriptional CDKs (CDK7 and CDK9) and cell cycle CDKs (CDK4 and CDK6) as well. In addition, we demonstrate that antiproliferative activity in ovarian cancer cells (OVCAR8) depends on CDK2 degradation and correlates with high expression of cyclin E1 (CCNE1), which functions as a regulatory subunit of CDK2. Collectively, our work provides evidence that TMX‐2172 represents a lead for further development and that CDK2 degradation is a potentially valuable therapeutic strategy in ovarian and other cancers that overexpress CCNE1. Abstract : Selective targeting of closely related members of the cyclin‐dependent kinase family remains difficult. Here, a heterobifunctional degrader molecule, TMX‐2172, is described. Dual degradation of CDK2 and CDK5 in OVCAR8 cells is achieved by reducing the binding affinity of the pyrimidine kinase inhibitor for CDK4, CDK6, CDK7, and CDK9, and by differential recognition between CDK2 and CDK1 mediated by the E3 ligase cereblon.